Competitive success factors of forwards in elite water polo - Maryin, I. S.; Stepanova, O. N.; Karpov, V. Yu.; Latushkina, E. N. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to rate the elite forwards` competitive swimming styles and patterns versus the team competitive success rates in modern top-level water polo. The authors made a content analysis of the 2016 Olympics video replays with application of the qualitative and quantitative performance rates to analyze the competitive swimming styles, patterns and the game actions and tactics of the elite forwards. It was found that the team competitive performance may be rated by the following criteria: (1) team standing on the tournament scoreboard; (2) goals scored; and (3) goals conceded. The study data were processed using data averaging, correlation and factor analyses to offer a statistical model of the competitive swimming styles and patterns applied by the elite water polo players. The study findings were used to offer the sets of swimming skills training exercises to model competitive performance of the elite forwards in modern water polo.